3D magnetotelluric modeling using high-order tetrahedral Nédélec elements on massively parallel computing platforms - Castillo-Reyes, Octavio; Modesto, David; Queralt, Pilar; Marcuello, Alex; Ledo, Juanjo; Amor-Martin, Adrian; de la Puente, Josep; García-Castillo, Luis Emilio (Computers & geosciences, 2022)
We present a routine for 3D magnetotelluric (MT) modeling based upon high-order edge finite element method (HEFEM), tailored and unstructured tetrahedral meshes, and high-performance computing (HPC). This implementation extends the PETGEM modeller capabilities, initially developed for active-source electromagnetic methods in frequency-domain. We assess the accuracy, robustness, and performance of the code using a set of reference models developed by the MT community in well-known reported workshops. The scale and geological properties of these 3D MT setups are challenging, making them ideal for addressing a rigorous validation. Our numerical assessment proves that this new algorithm can produce the expected solutions for arbitrarily 3D MT models. Also, our extensive experimental results reveal four main insights: (1) high-order discretizations in conjunction with tailored meshes can offer excellent accuracy; (2) a rigorous mesh design based on the skin-depth principle can be beneficial for the solution of the 3D MT problem in terms of numerical accuracy and run-time; (3) high-order polynomial basis functions achieve better speed-up and parallel efficiency ratios than low-order polynomial basis functions on cutting-edge HPC platforms; (4) a triple helix approach based on HEFEM, tailored meshes, and HPC can be extremely competitive for the solution of realistic and complex 3D MT models and geophysical electromagnetics in general. •Adaptive mesh design can be beneficial for the solution of the 3D MT problem.•High-order discretizations can offer excellent accuracy.•High-order basis achieve better parallel efficiency ratios than low-order basis.•Tailored meshes, HEFEM, and HPC can be extremely competitive for 3D MT modeling.•PETGEM is well suited to solve both active-source and passive-source EM methods